Choreography education in early XIX century Russia: a special educational model - Filanovskaya, Tatyana (Voprosy obrazovaniya / Educational Studies Moscow, 2013)
Author considers the second stage of the development of professional ballet education in Russia: from the beginning to the middle of the XIX century in the context of Romanticism. In the article some special and universal features of the educational model are delineated and socio-cultural factors that shape and sustain changes in the dance education as well as mechanisms which implement these changes are revealed.